Design Considerations on a Monolithically Integrated, Self Controlled and Regenerative 900 V SiC Circuit Breaker - Boettcher, N.; Erlbacher, Tobias (2020 IEEE Workshop on Wide Bandgap Power Devices and Applications in Asia, WiPDA Asia 2020, 2020)
This paper presents an in depth analysis of the design constraints of a novel monolithically integrated circuit breaker technology suitable for 900 V applications. The proposed topology is based on the dual thyristor concept, which poses exceptional design challenges. In order to understand the basic operation and influence of design parameters, an analytical dual thyristor model is derived. With the knowledge gained, (a) a monolithically integrated topology in 4H-SiC technology is developed and its characteristics are discussed in a design study with the aid of TCAD simulations. These simulations reveal designs exhibiting specific on-state resistance of 53 mOhmcm2, trigger current density of 149 A/cm2 and blocking voltage of 1252 V.
CRIS-Team Scopus Importer:2021-04-19